Analysis of the Relationship Between Attitude and Motivation and Medication Adherence Among Hypertensive Patients at Royal Prima General Hospital Medan - Natalia, Desi; Novriani, Erida; Lubis, Razoki (CV. Nusantara Scientific Medical, 2025)
Hypertension remains one of the leading causes of morbidity and mortality globally, with poor medication adherence being a key barrier to effective management. This study aimed to analyze the relationship between attitude and motivation with medication adherence in hypertensive patients at Royal Prima General Hospital Medan. A quantitative, cross-sectional approach was employed, involving 150 respondents selected via purposive sampling. Primary data were collected using validated questionnaires covering demographics, attitude, motivation, and medication adherence. Data were analyzed using SPSS version 25 through univariate and bivariate (Chi-square) methods. Results showed that 59.3% of respondents had a fair attitude, 44.0% had moderate motivation, and 75.3% adhered to their medication. Bivariate analysis revealed a significant relationship between attitude and adherence (p = 0.000), and between motivation and adherence (p = 0.016). Patients with better attitudes and higher motivation demonstrated higher compliance with antihypertensive therapy. These findings highlight that psychosocial factors like attitude and motivation play critical roles in influencing patient behavior. Interventions targeting these behavioral dimensions could substantially improve treatment adherence and long-term health outcomes in hypertensive patients. Healthcare professionals should incorporate patient education and motivational strategies into hypertension management to foster sustained adherence.